A institucionalização da pesquisa educacional no Brasil: estudo bibliométrico dos artigos publicados na Revista Brasileira de Estudos Pedagógicos 1944-74 - Lidia Alvarenga (1996)
This is a bibliometric study of journal articles which report the institutional development of Educational Research in Brazil, published in the Revista Brasileira de Estudos Pedagógicos (RBEP), from the Brazilian National Institute for Educational Studies and Research (Instituto Nacional de Estudos e Pesquisas Educacionais, INEP), from 1944 to 1974. A literature review of Educational Research in historical perspective is presented. The concepts of Science, Knowledge, Education Science, Educational Research, Research, Information Science, Bibliometrics, Citation and the specialized journal in the communication of knowledge are discussed, with special emphasis on the educational area. Additional concepts along with theoretical and methodological principles originating from several disciplines are also discussed. The objetives of this dissertation are essencially connected to the areas of Information Science and Educational Research: to develop a bibliometric analysis of the articles from RBEP; using the concepts and principles of Knowledge Archaeology, as described by Michel Foucault, to study journal articles and citation in a specific knowledge area; to study the behavior of a specialized journal through an investigation of its articles and citation patterns; to establish, through the journal literature, elements for the description of Educational Research institutional development. It is assumed that the specialized journal is a privileged source for the communication of knowledge in a subject area, and that a bibliometric study, built on the paradigms offered by Information Science, is an effective tool for the accomplishment of an archaeological work. An additional assumption is related to the polyphonic, intertextual, pragmatical and elitist patterns in a specific knowledge area, calling for the existence of exclusion and scattering systems in the knowledge communication process of Educational Research. Empiricist and gnosiological/epistemological categories build up the prospective view for the analysis of data, organized into two complementary strata: the journal articles and their citations. The results may contribute with new information for the description of the kind of knowledge that developed the institutional process of Educational Research in Brazil, mainly the role of RBEP, at the same time may be a source for the study of the record of knowledge production in the area, as well as of a concealing tool of important expressions on the subject, which due to political and ideological trends of the time remain dormant underneath the publication process.